Economic Empowerment Of The Community Through Optimizing The Understanding Of Financial Statements (MSMEs Bojongsoang Village Bandung) - Asri Suangga; Riyang Mardini; Rini Lestari; Rudy Hartanto; Annisa Nadiyah Rahmani; Boyke Rahmat Ramdani; Alia Alifa Ibrahim (Kajian Akuntansi, 2022)
Financial recording and reporting training is expected to be able to overcome internal problems related to accountability that are often faced by MSMEs. The right assistance will help MSMEs to develop, from micro, small, to medium scale,can even be the forerunner of the emergence of large-scale industry. This research was conducted on MSMEs who are members of the "Someah" community, Bojongsoang Village, Bandung Regency, West Java Province, the majority of which are engaged in food and beverage, as well as handicrafts. The purpose of this study is to assist MSME partners in understanding the importance of recording financial statements, and analyzing financial statements. The research method used is descriptive qualitative. The results showed that in general, MSME actors in Bojongsoang Village did not have good and correct accounting and bookkeeping knowledge. However, with this assistance, participants understand more about accounting and recording financial statements better.Pelatihan pencatatan dan pelaporan keuangan diharapkan dapat mengatasi permasalahan internal terkait akuntabilitas yang sering dihadapi oleh UMKM. Pendampingan yang tepat, akan membantu UMKM untuk berkembang, dari skala mikro, kecil, hingga menengah, bahkan bisa menjadi cikal bakal munculnya industri skala besar. Penelitian ini dilakukan pada UMKM yang tergabung dalam komunitas “Someah” Desa Bojongsoang Kabupaten Bandung Provinsi Jawa Barat yang mayoritas bergerak di bidang makanan dan minuman, serta kerajinan tangan. Tujuan penelitian ini adalah membantu mitra UMKM dalam memahami pentingnya pencatatan laporan keuangan, dan menganalisis laporan keuangan. Metode penelitian yang digunakan adalah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa secara umum pelaku UMKM di Desa Bojongsoang belum memiliki pengetahuan akuntansi dan pembukuan laporan keuangan yang baik dan benar. Namun dengan adanya pendampingan ini peserta lebih mamahami tentang akuntansi dan pencatatan laporan keuangan lebih baik lagi.